Exploring Local Maize Diversity for Increased Agricultural Sustainability: New Insights into Drought Stress Response and Recovery of Guinea-Bissau Landraces - Teixeira, Manuela (2021)
Landraces are rightfully known as the backbone of sustainable food production, particularly in areas experiencing significant environmental constraints. However, protecting landraces from genetic erosion and valuing their potential for plant breeding and sustainable food production requires in-depth understanding of their phenotypic traits. Two Guinea-Bissau landraces (GA, GV) and two elite cultivars (P98438, P0023) were subjected to drought stress for 7 (S1) and 12 (S2) days. After this period plants were rewatered (R). The relative water content (RWC) was unchanged in S1 and decreased in S2 in all genotypes. Chlorophyll a fluorescence parameters changed moderately in S1 and remarkably in S2, including on GA and GV plants, where a decrease of Fv/Fm and PI, and an increase in absorbed, trapped, and dissipated energy per reaction center, was found. P0023 plants showed the most contrasting behavior to Guinea-Bissau genotypes, presenting an increase in Fv/Fm and PI values and a decrease in the specific energy fluxes per reaction center (RC), whereas P9838 presented an intermediate behavior. Drought (S1 and S2) decreased the amount of chlorophyll (Chl.) and carotenoids in GA and GV plants. On the contrary, in the P0023, the only pigment to decrease with stress was Chl. b. Fatty acid (FA) analyses allowed for the identification of C16:0, C18:2, and C18:3 in larger amounts, and C14:0, C16:1t, C18:0, and C18:1 acids in lower abundance. Drought stress decreased C18:3, the double bond index, and the total FA (except for P0023 and GV in S2) and increased C14:0 and C16:0 acids. The expression of phospholipase D (PLD) was higher at S2. After recovery, PLD expression presented a notorious decrease on the Guinea-Bissau landraces. P0023 showed the smallest alterations after recovery, while Guinea’s plants suffered more radical alterations leading to the conclusion that Guinea’s landraces were more drought-sensitive and that their recovery rate was impaired.